2013
DOI: 10.9745/ghsp-d-13-00025
|View full text |Cite
|
Sign up to set email alerts
|

Building on safety, feasibility, and acceptability: the impact and cost of community health worker provision of injectable contraception

Abstract: This project in Zambia contributes to our understanding of the impact of community-based provision of injectables on method choice and uptake and of the costs of adding DMPA to an established community-based family planning program. The project also illustrates the importance of involving stakeholders from the outset, analyzing costs relevant to scale up, and engaging in policy change dialogue not at the end, but rather throughout project implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 4 publications
0
54
0
Order By: Relevance
“…Furthermore, although community-based provision of injectables by CHWs is a safe, acceptable, and effective way to increase access to family planning in LMICs, studies of such interventions in Kenya and Zambia found relatively high 12 month discontinuation rates of 32% and 37%, respectively. [12][13][14] A 2013 Cochrane review of interventions to increase continuation rates of hormonal methods of contraception 15 identified only one study with a positive effect on continuation; however, the evidence for this intensive counselling intervention, which provided women with audiovisual messaging at each follow-up visit, was categorised as "low grade". 15 Another study identified in that review examining the role of counselling on oral contraceptive continuation found an effect only when counselling was coupled with phone calls.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…Furthermore, although community-based provision of injectables by CHWs is a safe, acceptable, and effective way to increase access to family planning in LMICs, studies of such interventions in Kenya and Zambia found relatively high 12 month discontinuation rates of 32% and 37%, respectively. [12][13][14] A 2013 Cochrane review of interventions to increase continuation rates of hormonal methods of contraception 15 identified only one study with a positive effect on continuation; however, the evidence for this intensive counselling intervention, which provided women with audiovisual messaging at each follow-up visit, was categorised as "low grade". 15 Another study identified in that review examining the role of counselling on oral contraceptive continuation found an effect only when counselling was coupled with phone calls.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“… 7–10 Based on the assumption that workers at the grassroots level are more accessible and acceptable to users in their communities, they are expected to improve access and coverage to basic health services. 9 11 …”
Section: Introductionmentioning
confidence: 99%
“…Women like the freedom from having to remember daily use and discretion afforded by injectable contraception . Providers also seem to prioritize injectables in some countries over other methods, because they require less frequent clinic visits and can be provided by less skilled service providers . Like preferences for injectable contraception, women in multiple settings have expressed preferences for an injectable PrEP product, which they perceived to last longer, require less medical intervention, have lower use burden and enable more discreet use .…”
Section: Discussionmentioning
confidence: 99%